Effects of pre-medication with acepromazine/midazolam/ dexmedetomidine and butorphanol on induction dose of propofol and incidence of apnoea during induction in canines - KUMAR, RAJESH; AAKANKSHA; TIWARY, RAMESH; VERMA, N K; SAXENA, A C; HOQUE, M (The Indian Journal of Animal Sciences, 2022)
The objective of the study was to evaluate the effect of ACE, MID, DEX (IM) and DEX (IV) with butorphanol on quality of induction, induction dose of propofol and incidence of apnoea during anaesthesia in client-owned dogs. Animals were randomly divided into four groups. After pre-medication with atropine sulphate, animals were administered with ACE @ 0.05 mg/kg b.wt IV in group A, MID @ 0.5 mg/kg IV b.wt in group B, DEX @ 15 μg/kg IM b.wt in group C and DEX @ 15 μg/kg IV b.wt in group D along with butorphanol @ 0.2 mg/kg b. wt. I/V. All animals were induced with propofol and maintained with isoflurane till the end of closing last skin suture. Adequate sedation and depth of analgesia was observed in the animals of the all four group and this sedation made handling of the animals proper and safe before induction. Significantly lower dose of propofol was needed for induction in the grous C and D as compared to groups A and B. Incidence of temporary apnoea in groups A and B was 10%, whereas in groups C and D was 30%, but they were managed by assisted ventilation and smoothly maintained with isoflurane without complication. It was found that ACE/MID/DEX with butorphanol has dose-sparing effect and provides adequate sedation and analgesia in the canines. Chances of apnoea may be more with DEX pre-medication, but they can be managed by assisted ventilation without any complication.